2000
DOI: 10.1016/s0730-725x(00)00179-x
|View full text |Cite
|
Sign up to set email alerts
|

Mealiness assessment in apples and peaches using MRI techniques

Abstract: Mealiness (woolliness in peaches) is a negative attribute of sensory texture that combines the sensation of a desegregated tissue with the sensation of lack of juiciness. In this study, 24 apples cv. Top Red and 8 peaches cv. Maycrest, submitted to 3 and 2 different storage conditions respectively have been tested by mechanical and MRI techniques to assess mealiness. With this study, the results obtained on apples in a previous work have been validated using mathematical features from the histograms of the T2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 6 publications
2
29
0
3
Order By: Relevance
“…As with the nonspatially resolved relaxation data, it was found that the T 2 decreased with increasing mealiness and that at a certain point a broad change in the histogram shape was observed and corresponds to a signifícant increase in the standard deviation of the T 2 valúes within the apple. These MRI features therefore agreed with expectations on the basis of previous research work [1,2]. It is interesting to note that the T 2 map of apple CO-25 also features a tailed T 2 histogram and this apple also showed an abnormal variability in texture reference valúes.…”
Section: Results Of the Mri And Nmr Relaxometry At Ucmsupporting
confidence: 89%
See 2 more Smart Citations
“…As with the nonspatially resolved relaxation data, it was found that the T 2 decreased with increasing mealiness and that at a certain point a broad change in the histogram shape was observed and corresponds to a signifícant increase in the standard deviation of the T 2 valúes within the apple. These MRI features therefore agreed with expectations on the basis of previous research work [1,2]. It is interesting to note that the T 2 map of apple CO-25 also features a tailed T 2 histogram and this apple also showed an abnormal variability in texture reference valúes.…”
Section: Results Of the Mri And Nmr Relaxometry At Ucmsupporting
confidence: 89%
“…Following previous research work [2] these data were used to calcúlate the following subsidiary parameters: The average, standard deviation, máximum and minimum T 2 valúes were calculated from the global T 2 maps (disregarding those pixels corresponding to the background or the core). The T 2 histograms were used to derive the lower quartile (T 2 lower limit containing 25% of pixels of the histogram), upper quartile (T 2 upper limit containing 25% of pixels of the histogram), T 2 mode (most frequent valúes), mode height (number of pixels with T 2 valué equal to the mode), interquartile range (difference between upper and lower quartiles), first shape coefficient (mode height/interquartile range), and second shape coefficient (0.5 times the number of pixels of the histogram/interquartile range).…”
Section: Magnetic Resonance Imaging (Ucm-upm)mentioning
confidence: 99%
See 1 more Smart Citation
“…NMR technology can provide better images of the internal structure of intact fruits and vegetables, and thus, it is suitable for detecting internal defects and quality issues such as decay and maturity (Barreiro et al, 2000) (Barreiro et al, 2004). 1 H-MRI technology can stimulate the RF-absorbing ability of fruits and vegetables as they have a multitude of proton-containing species .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the storage conditions, harvesting date and fruit size also influence the development of mealiness. Apples of larger size or of late harvest are more susceptible to mealiness (Barreiro et al, 2000;De Smedt, 2000). Hatfield and Knee (1988) and De Smedt et al (1998) concluded that the cells in mealy apples become more rounded, and, as a consequence, the amount of apoplast is larger in mealy apples than in fresh apples.…”
Section: Introductionmentioning
confidence: 99%